2018
DOI: 10.2147/jpr.s163044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pain, abstraction, and self-control: being in pain makes it harder to see the forest for the trees and is associated with lower self-control

Abstract: ObjectivesAlthough abstract thinking is a fundamental dimension of human cognition, it has received scant attention in research on pain and cognition. We hypothesized that physical pain impairs abstraction, because when people experience pain at high intensity levels, attention becomes concretely focused on the self in the here and now, where little else matters than finding relief for the pain they are currently experiencing. We also examined the relationship between pain and self-control, predicting that pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…It is possible that naturally-occurring pain would influence reasoning Reasoning in pain 31 behaviour in a way that experimental pain did not in these experiments. Recent studies have found that while experimental pain did not change abstract thinking behaviour [1], the intensity of clinical pain did [23]. The benefit of using experimental pain is that we can isolate the effects of pain from the effects of confounds such as other health problems, depression, and pain-related anxiety.…”
Section: Reasoning In Pain 30mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that naturally-occurring pain would influence reasoning Reasoning in pain 31 behaviour in a way that experimental pain did not in these experiments. Recent studies have found that while experimental pain did not change abstract thinking behaviour [1], the intensity of clinical pain did [23]. The benefit of using experimental pain is that we can isolate the effects of pain from the effects of confounds such as other health problems, depression, and pain-related anxiety.…”
Section: Reasoning In Pain 30mentioning
confidence: 99%
“…There is evidence that pain disrupts attention [4; 6-8; 27; 32; 33; 44; 46], but the impact of pain on higher-level cognitive processes is less-investigated (although see [1,23,28]). It is unclear whether we should expect higher-level tasks to also be affected by pain.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the effects of pain on higher-level cognition. One which did, found that clinical pain was associated with less-abstract thinking [20], while another found no evidence that experimentally-induced pain affected abstract thinking [2]. Here, we focus on the potential impact of pain on higher-level real-world cognitive tasks requiring attention, namely numerical reasoning and decision making, which have serious consequences if one gets them wrong.…”
Section: Introductionmentioning
confidence: 98%
“…The reason for this is that differences in the duration and persistence of pain could affect the brain differently, even in patients within the chronic pain group. 4,22,24 Impaired logical reasoning could be detrimental to both the society and the individual with pain. If it is found that clinical, musculoskeletal pain impairs logical reasoning, the effects could have nontrivial consequences for life domains, such as education, problem solving, and risk assessment.…”
Section: Introductionmentioning
confidence: 99%